PENGEMBANGAN MODUL PEMBELAJARAN BAHASA INDONESIA BERBANTUAN PETA PIKIRAN PADA MATERI MENULIS MAKALAH SISWA KELAS XI SMA/MA - Mina Syanti Lubis; Syahrul R; Novia Juita (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: The aim of this research is to produce a module of Indonesian language learning material with mind mapping in writing paper ability which are valid, practice, and effective to be used by the XI grade students of SMA/MA. This research tends to research and development research by using 4-D model of development. Development activities are started by identification, design, and development. Data of this research belongs to quantitative that is got by assessment of valuator, Indonesian teacher, students, and the result of students in learning Indonesian. Based on the analysis and discussion of data, the writer gives many conclusions. First, validation of module of Indonesian language learning material with mind mapping in writing paper ability at the XI grade students of SMA Negeri 1 Batangtoru tends to very valid with 94,89. Second, practicability of the modul can be said as very practice with 81.71. Third, effectiveness of the module tends to very effective with 86,74 from students and completeness show the result of learning is good category or 76.85 (34 students from 39 students). Therefore, it can be concluded that the module which is developed can be used as learning material in the school, especially for the XI grade students of SMA Negeri 1 Batangtoru in writing paper ability. Key Words: learning module, mind map, writing paper.